070 A pilot study assessing choroidal thickness in frontotemporal dementia and motor neuron disease. Issue 6 (27th May 2022) - Chen, Yingdi; Larraz, Juan; Wong, Michael; Pearson, Tom; Kalam, Sabrina; Glasmacher, Stella; Davenport, Richard; Newton, Judy; Pal, Suvankar; ,
Abstract : Background: Frontotemporal dementia and motor neurone disease are neurodegenerative disorders known to occur on a clinical continuum and to share underlying genetic and neuropathological char- acteristics. Retinal choroidal thickness (RCT) has been reported as a marker for inflammatory diseases. By comparing RCT between these disorders, this study aims to investigate the value of RCT in subclinical inflammation. Methods: Spectral domain optic coherence tomography (SD-OCT) images were analysed to evaluate RCT in 38 people with FTD(pwFTD) (median age 65(9)), 29 with MND (pwMND) (median age 66(15)) and 31 healthy controls (median age 54(20)). The regression of RCT with age was compared amongst the three groups. Results: 1) Accelerated choroidal thinning was found in pwMND in all choroidal locations, but only identified in the sub-fovea area of the pwFTD group. 2) Compared to age matched pwMND and healthy controls, choroidal thickness was significantly lower in the temporal region of pwFTD patient aged under 65 year. Conclusion: This study demonstrates an increase in rate of choroidal thinning in MND and FTD. Measurement of RCT using OCT may be a useful non-invasive surrogate biomarker to monitor subclinical inflammation and has potential for use as a secondary outcome measure in clinical trials of disease modifying treatments. ychen112@ed.ac.uk 60